2021
DOI: 10.1109/jeds.2021.3100290
|View full text |Cite
|
Sign up to set email alerts
|

Variability Study of Ferroelectric Field-Effect Transistors Towards 7nm Technology Node

Abstract: The random variation sources have a significant influence on the performance of ferroelectric field-effect transistor (FeFET). In this work, comparative analysis on the process variation induced variability of FeFET towards a 7 nm technology node has been conducted, including different device structures from bulk to FDSOI and FinFET. The random ferroelectric/dielectric phase variation (PV), the metal work function variation (WFV) and the line-edge roughness (LER) effects are incorporated in TCAD simulations to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Other sources of variation such as the random dopant fluctuations (RDF) and fabrication tolerances can affect the FeFET variability. [ 77 ] The V th can also vary due to the random FE to dielectric phase ratio variation, metal electrode work function variation, line edge roughness effects, and charging/discharging of interface traps during the write operation. The variability sources can vary depending on the FeFET structure type: planar FeFETs are affected by the work function variation as opposed to the FinFeFETs where the fin line‐edge roughness is important for the variability.…”
Section: Memory‐based Applications Of Fluorite‐structured Materialsmentioning
confidence: 99%
“…Other sources of variation such as the random dopant fluctuations (RDF) and fabrication tolerances can affect the FeFET variability. [ 77 ] The V th can also vary due to the random FE to dielectric phase ratio variation, metal electrode work function variation, line edge roughness effects, and charging/discharging of interface traps during the write operation. The variability sources can vary depending on the FeFET structure type: planar FeFETs are affected by the work function variation as opposed to the FinFeFETs where the fin line‐edge roughness is important for the variability.…”
Section: Memory‐based Applications Of Fluorite‐structured Materialsmentioning
confidence: 99%
“…It is important to recollect that the previously discussed variability issues related to the FE-HfO2 layer add up to the variability sources of the underlying MOSFET (e.g., randomdopant fluctuations, RDF, line edge roughness, LER, workfunction fluctuations, WFF) which in practice might also limit the distinguishability of memory states depending on the transistor dimensions and technology node. So far, only a few studies have been devoted to analyze the impact of traditional variability sources on the performance of FeFETs for both logic [130], [131] and memory [132] applications. A recent study found that while MOSFET-related variability are enhanced by higher Ps (i.e., saturated polarization), Pr, and EC values, the random distribution of these parameters (due to non-uniform FE-HfO2) are much more affecting the VTH's distribution of the analyzed FeFETs [133].…”
Section: Variabilitymentioning
confidence: 99%
“…Device-to-device variation is one of the key challenges for FeFET scaling as the increased variation degrades the MW of scaled devices. There were mainly three kinds of variation sources in FeFET [266] : 1) intrinsic FE variation due to reduced number of domains and FE switching stochasticity; 2) extrinsic FE variation arising from the distributions of FE parameters, namely, P s and E c as well as FE/DE composition; 3) underlying transistor variation including random dopant fluctuation (RDF), line-edge roughness (LER), metal work function variation (WFV), interface trap (IFT) and so on. The impacts of these variation sources were evaluated with TCAD tools [222, 266−268] .…”
Section: Variationmentioning
confidence: 99%